2010
DOI: 10.1007/s10549-010-0818-y
|View full text |Cite
|
Sign up to set email alerts
|

Absence of genomic BRCA1 and BRCA2 rearrangements in Ashkenazi breast and ovarian cancer families

Abstract: A substantial proportion of Ashkenazi Jewish (AJ) breast and ovarian cancer families carry one of three founder mutations in BRCA1 (185delAG, 5382InsC) and BRCA2 (6174delT). Non-founder mutations are identified in another 2-4% of such families. The extent to which major genomic rearrangements in BRCA contribute to breast and ovarian cancer in the Ashkenazim is not well understood. We identified AJ individuals with breast and/or ovarian cancer undergoing hereditary breast/ovarian cancer risk assessment since 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
2
5
0
1
Order By: Relevance
“…Large rearrangements were not identified in the BRCA1/2 genes (n=26) in our cohort of AJ individuals testing negative for founder and non-founder point mutations, which is consistent with previous reports (Palma et al 2008;Stadler et al 2010). These data are consistent with prior studies showing that founder mutations continue to account for the vast majority of all mutations in this population and suggest that routine screening for large rearrangements does not seem to be warranted in AJ individuals.…”
Section: Practice Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…Large rearrangements were not identified in the BRCA1/2 genes (n=26) in our cohort of AJ individuals testing negative for founder and non-founder point mutations, which is consistent with previous reports (Palma et al 2008;Stadler et al 2010). These data are consistent with prior studies showing that founder mutations continue to account for the vast majority of all mutations in this population and suggest that routine screening for large rearrangements does not seem to be warranted in AJ individuals.…”
Section: Practice Implicationssupporting
confidence: 92%
“…The prevalence of these three mutations is between 1.1 and 2.7 % in AJ populations unselected for personal or family cancer history (Metcalfe et al 2010;Neuhausen et al 1996;Roa et al 1996;Struewing et al 1997), and 10.2 % for AJ individuals with a family history of breast or ovarian cancer (Malone et al 2006). Of those who do not carry one of the three founder mutations, approximately 0.6-4.0 % have been found to harbor a nonfounder BRCA1/2 mutation (Frank et al 2002;Kauff et al 2002;Phelan et al 2002), and large genomic rearrangements in AJ individuals are reported to be rare (Palma et al 2008;Stadler et al 2010;Distelman-Menachem et al 2009;Walsh et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of pathogenic alterations that escape most of the current gene sequencing-based diagnostic approaches were proposed, including partial or complete exon losses or duplications resulting in an out-of-frame translation and a mutant peptide with abnormal structure and/or function ( Petrij-Bosch et al , 1997 ; Ewald et al , 2009 ). Several reports confirmed that BRCA rearrangements, particularly in BRCA1 , are indeed quite frequent in HBOC families from selected countries ( Preisler-Adams et al , 2006 ; Hansen et al , 2008 ; Kang et al , 2010 ; Ratajska et al , 2008 ; Stadler et al , 2010 ; Rudnicka et al , 2013 ; Pal et al , 2014 ). These mutations are scattered throughout the gene and although most of them are deletions, duplications and triplications, as well as combined deletion/insertion events have also been described.…”
Section: Introductionmentioning
confidence: 82%
“…To date, at least 81 different large genomic rearrangements have been found in BRCA1 gene and account for 8%–27% of all BRCA1 mutations. Alternatively Alu sequences are less common in BRCA2 gene, where only few large genomic rearrangements are reported, accounting for 0%–11% of all BRCA2 mutations [19-21]. …”
Section: Resultsmentioning
confidence: 99%